THE ROLE OF RETAINER AS PREVENTIVE IN POST-ORTHODONTIC TREATMENT RELAPS - Gufa Bagus Pamungkas (Universitas Muhammadiyah Semarang, 2022)
Orthodontic treatment is a very complex process because throughout human life the teeth will continue to change position due to their main function which plays an important role in the mastication process, so that when the periodontal tissue and teeth are under pressure after orthodontic treatment, it is very easy for the teeth after orthodontic treatment to relapse or return to the original position before orthodontic treatment until the maximum remodeling process is achieved, the remodeling process takes at least 6 months, therefore a tool or device is needed that can be used to maintain the position of the teeth after orthodontic treatment, namely a retainer, because the success of orthodontic treatment itself will not be achieved if the tooth returns to the original arch and position.